2006
DOI: 10.1007/s10832-006-6359-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vanadium doping on ferroelectric and electrical properties of Bi3.25La0.75Ti3O12 thin film

Abstract: Bi 3.25 La 0.75 Ti 3 O 12 (BLT) and V-doped BLT (BLTV) thin films were prepared on Pt/Ti/SiO 2 /Si substrates by a pulsed laser deposition method. The effects of V doping on ferroelectric and electrical properties were investigated by polarization-electric field hysteresis loops and leakage current-voltage measurements. BLTV single phases were confirmed by X-ray diffraction. Remnant polarization was increased and the leakage current density was decreased by V doping. The leakage current density of BLT thin fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…A number of other studies have reported that doping with impurity donors has been correlated with a drop in the leakage current [15][16][17], as we also found with V-doping. The earlier studies attributed the reduction in leakage current with a drop in the oxygen vacancy concentration [16,17].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…A number of other studies have reported that doping with impurity donors has been correlated with a drop in the leakage current [15][16][17], as we also found with V-doping. The earlier studies attributed the reduction in leakage current with a drop in the oxygen vacancy concentration [16,17].…”
Section: Resultssupporting
confidence: 84%
“…The addition of donors such as La 3+ at the Ba site 15 and Nb 5+ at the Ti 4+ site 16 in BaTiO 3 significantly reduces the leakage current. This trend is also observed in another titanate, Bi 3.25 La 0.75 Ti 3 O 12 [17]. The J À E !…”
Section: Resultssupporting
confidence: 68%
“…In this work, the Ohmic conduction process dominates in a low electric field at room temperature, which is similar to that of other ferroelectric thin film. [22][23][24] With increasing temperature, the leakage current density is described by the Schottky and Poole-Frenkel emission. Previously, many researchers reported the conduction process for ferroelectric thin films.…”
Section: Leakage Current Characteristics Of Knn10:ln By Schottky and ...mentioning
confidence: 99%